Elementos multimodais na dialogia mãe-bebê em contextos de riso - Lima, Valdenice Pereira de (2016)
The multimodality in acquisition is an approach that is increasingly discussed among those who are interested in child development. That perspective considers as linguistic, those interactive behaviors done by babies, like gesticulations, face expressions and the way of watching. This research studies the multimodality, focus on the child`s smile, from 16 to 24 months old. The main objective of this work is to investigate how the children smile, related to the multimodal point of view, how they make the interaction with the others, and also to understand how this role helps for their language acquisition. Related to other previous researches on this subject, we found that most of them are focus on smile in adults, with just few researches with emphasis on the first years of babies´ life, like Del Ré (2002, 2003, 2005), discussing the smile in the mood during language acquisition. Therefore, in this study, we observed that the construction of the smile in the language acquisition phase, as seen this feature in the multimodal optical, used by infants, makes a relevant situation for the child during the language consolidation. As a theoretical basis for this study, we used theories on laughter (BERGSON, 2007; BAKHTIN, 2000; MENDES & SEIDL DE MOURA; DEL RÉ, 2002, 2003, 2005) and the multimodality language acquisition (MCNEILL, 1985, 2000; GOLDIN-MEADOW, 1999; KENDON, 2000; FONTE, 2011). For the development of this thesis, we did a longitudinal study, whose main object has been composed for mother-baby interaction recorded in videos, in the most natural way possible. The analyzed data was transcript in the ELAN software, which made possible to investigate the emergence of multimodality in a simultaneous way. Thus, this software can describe the relationships built among the subjects analyzed. We started from the hypothesis that the routines involving laughter will be constituted by multimodality, guided by the dialogic movement between the adult and the child. Our data showed that the interactive situation are created with multimodality, and that the smile acts as a relevant element in the routines consolidation; we realized also that the context of smile are made dialogically, by engaging both the mother and the child in the analyzed scenes. Those results confirm our hypothesis that the child uses the smile as a multimodal element in order to establish interaction with those around him.